Отримання поліцейськими практичних навичок із вогнепальною зброєю в сучасних реаліях та під час воєнного стану - Владимиров, М. В.; Vladymyrov, M. V.; Балац, А. О.; Balats, A. O.; Пустовий, Ю. Ю.; Pustovyi, Yu. Yu.; Підгайна, В. В.; Pidhaina, V. V.; Максим Владимиров; Анатолій Балац; Юрій Пустовий (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 1. - С. 351-361, 2023)
Проаналізовано підготовку поліцейських у поводженні з вогнепальною зброєю згідно з керівними документами, розробленими до початку повномасштабної російської агресії. Встановлено аспекти, які враховують досвід і знання кандидатів до Національної поліції перед навчанням у закладах вищої освіти МВС України. Досліджено напрями покращення якості отримання знань із вогневої підготовки, які впливають на готовність поліцейського до захисту країни. Розглянуто питання щодо сприяння патріотичному вихованню та розвитку спеціальних закладів освіти для підготовки майбутніх поліцейських.

The article presents the results of a scientific study, namely, the analysis of police training in firearms handling in accordance with the guidelines developed in peacetime before the beginning of Russian aggression. The author identifies the aspects that directly contribute to the selection of candidates for service in the national police, taking into account their previous experience and knowledge of firearms handling before starting their studies at higher educational institutions of the Ministry of Internal Affairs of Ukraine with specific training conditions. The author identifies promising areas of work to improve the quality of knowledge in the discipline “Firearms Training”, which directly affects the readiness of a police officer to protect the country and who must have practical skills in the use of modern weapons. The importance of strengthening the country’s defense capabilities and preparing young people to defend the homeland, as well as martial law as a special legal regime in exceptional circumstances when there is a threat of an armed attack on the country, is considered. The issues of promoting patriotic education and the development of special educational institutions for training future police officers were highlighted, and the need to improve the material and technical base, in particular, the importance of developing computer technologies and other modern teaching methods that will maximize the effect of the educational process in the training of law enforcement officers, was emphasized. The article gives an example which, in our opinion, should be further developed and applied in higher educational institutions of the Ministry of Internal Affairs in the course of firearms training, which will increase the motivation of students and cadets not only to obtain positive marks in the firearms training course, but also to achieve a high level of sports and professional skills. Namely, the regular holding of practical shooting competitions. All of these measures are aimed at strengthening the country’s defense capabilities and raising the level of professional training of police officers, which is important for ensuring national security and protecting Ukraine’s national interests.

Проанализирована подготовка полицейских в обращении с огнестрельным оружием согласно руководящим документам, разработанным до начала полномасштабной российской агрессии. Установлены аспекты, учитывающие опыт и знание кандидатов в Национальную полицию перед обучением в высших учебных заведениях МВД Украины. Исследованы направления улучшения качества получения знаний по огневой подготовке, влияющих на готовность полицейского к защите страны. Рассмотрены вопросы содействия патриотическому воспитанию и развитию специальных учебных заведений для подготовки будущих полицейских.
Gaining practical skills in handling firearms in modern realities and under martial law
Keywords: вогнепальна зброя; навички поліцейських; поліцейські; вогнева підготовка; навчання правоохоронців; законодавство; відбір кандидатів; кульова стрільба; воєнний стан; firearms; police skills; firearms training; law enforcement training; legislation; selection of candidates; shooting; martial law; огнестрельное оружие; навыки полицейских; полицейские; огневая подготовка; обучение правоохранителей; законодательство; отбор кандидатов; пулевая стрельба; военное положение